2020
DOI: 10.1186/s12876-020-01472-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low skeletal muscle mass index and perioperative blood transfusion on the prognosis for HCC following curative resection

Abstract: Background This study aimed to assess the prognostic factors including low skeletal muscle mass index (SMI) and perioperative blood transfusion for patients with hepatocellular carcinoma (HCC) following curative surgery. Methods This study included 139 patients with HCC who underwent hepatectomy between 2005 and 2016. Univariate and multivariate analyses were performed to identify variables associated with overall survival (OS) and recurrence-free survival (RFS). Results Low SMI was significantly related w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Regarding specifically postoperative transfusions, low Hgb and incurring a major postoperative complication are logical causes of requiring a transfusion, for which sarcopenia was not an independent predictor. Despite an unclear cause, the link between sarcopenia and transfusion requirements has been similarly documented in other investigations 30‐33 …”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Regarding specifically postoperative transfusions, low Hgb and incurring a major postoperative complication are logical causes of requiring a transfusion, for which sarcopenia was not an independent predictor. Despite an unclear cause, the link between sarcopenia and transfusion requirements has been similarly documented in other investigations 30‐33 …”
Section: Discussionmentioning
confidence: 55%
“…Because of these, we hypothesize that sarcopenic patients have reduced total blood volume compared to nonsarcopenic patients. As a result, they may experience greater proportional blood loss and increased transfusion requirements from surgery 30‐33 . To delineate this relationship and identify those patients at risk for transfusion, we sought to investigate sarcopenia and its effect on transfusion requirements with head and neck cancer free flap reconstruction (HNCFFR) where transfusions are highly prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that body composition is closely associated with the survival of patients with several malignancies. Bekki et al found that hepatocellular carcinoma patients with a low skeletal muscle index (SMI) prior to surgery had poor OS [ 21 ]. Preoperative SMI can serve as an independent disease recurrence indicator in colon cancer [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cases with rHCC cases are increasing year by year in Asia, and hemorrhagic shock is more likely to occur after simultaneous rupture. Therefore, the proportion of blood transfusions is more likely to be higher than that of patients with nonruptured HCC; hence, it is all the more necessary to discuss the effect of PBT on the postoperative prognosis of rHCC ( 16 20 ). Many studies have reported that PBT increases the incidence of complications in patients after tumor surgery and that it also increases the risk of postoperative recurrence, which is related to immunosuppression due to blood transfusion ( 21 25 ).…”
Section: Discussionmentioning
confidence: 99%